Acute toxicity of insecticide thiamethoxam to crayfish (Astacus leptodactylus): Alterations in oxidative stress markers, atpases and cholinesterase - Uçkun, Miraç; Yoloğlu, Ertan; Uçkun, Aysel Alkan; Öz, Özden Barım (Slovensko Kemijsko Drustvo, 2021)
Thiamethoxam (Thmx) is a globally used neonicotinoid pesticide contaminated in freshwater ecosystems with residues detected in fishery products. Astacus leptodactylus is a popular freshwater crustacean that is cultivated and exported in many countries. In this study, we investigated the acute toxic effects of Thmx on A. leptodactylus using various biomarkers (acetylcholinesterase, carboxylesterase, glutathione S-transferase, glutathione, superoxide dismutase, glutathione peroxidase, glutathione reductase, and adenosinetriphosphatases). The 96-h LC50 value of Thmx was calculated as 8.95 mg active ingredient L-1. As the dose of Thmx increased, oxidative stress was induced by the inhibition/activation of antioxidant enzymes, while the activities of acetylcholinesterase, carboxylesterase and adenosinetriphosphatases were inhibited. As a result, it can be said that Thmx has highly toxic effects on crayfish, therefore they are under threat in the areas where this pesticide is used. © Except when otherwise noted, articles in this journal are published under the terms and conditions of the Creative Commons Attribution 4.0 International License
Keywords: Acetylcholinesterase; Antioxidant enzymes; Crustacean; Insecticide; Metabolic enzymes; Toxicity